Reconstructing The Regulation Of The Empty Box In Single-Candidate Pilkada Based On Electoral Law Justice - Moh. Maskurudin Hafid (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The phenomenon of regional elections with a single candidate in Indonesia continues to increase and raises serious problems for the quality of local democracy. The Constitutional Court Decision Number 100/PUU-XIII/2015 has provided constitutional legitimacy for "empty boxes" as a legitimate choice of voters, which was then accommodated in Law Number 10 of 2016. However, the recognition has not been followed by adequate administrative arrangements. In contrast to candidate pairs who have complete legal and institutional tools, blank boxes do not have the status of formal legal subjects, thus creating a void in arrangements related to representation, facilitation, supervision, funding, legal protection, and dispute resolution. This condition creates inequality of contestation and weakens the principle of level playing field in the single-candidate Regional Elections. This research is normative legal research with legislative, case, conceptual, and historical approaches. Legal materials are analyzed qualitatively through the identification of legal gaps, regulatory gaps, and implementation gaps, and using electoral law justice theories which are built on three main dimensions: legal certainty, equality of contestation, and protection of political rights. This study examines the legal position of empty boxes after the Constitutional Court Decision Number 100/PUU-XIII/2015, the impact of regulatory voids on electoral justice, and the model of restructuring its arrangements. The results of the study show that the main problem no longer lies in the legality of empty boxes, but in the incompleteness of the regulatory design. The void causes legal uncertainty and inequality between a single candidate supported by a full institutional apparatus and an empty box that is only present as a symbol on the ballot. Therefore, this study offers a reconstruction model based on limited administrative representation for the support group of empty boxes through multi-level arrangements in the Regional Election Law, KPU Regulations, Bawaslu Regulations, and technical guidelines for implementation. This reconstruction includes the facilitation of neutral information, limited recognition of support groups, funding accountability, supervision, legal protection, and limited objection and dispute mechanisms. The model is expected to strengthen legal certainty, maintain the integrity of local democracy, and realize electoral justice in single-candidate elections